Enhancing Vocational Education Through Digital Marketing Strategies: A Prototype Approach - Yullindo; Nandra; Idris, Iswandi (AI Society & STMIK Indonesia, 2024)
This study investigates the challenges faced in digital marketing transformation within vocational education at Politeknik LP3I PSDKU Campus Padang. The problem stems from traditional marketing methods being less effective in attracting prospective students in a digital era. Employing the Software Development Life Cycle (SDLC) prototype methodology, the research aims to develop a responsive marketing information system tailored to user needs. Objectives include identifying key marketing tools and enhancing user engagement through interactive platforms. Results demonstrate improved enrollment figures and user satisfaction, validating the effectiveness of digital marketing strategies. The findings contribute to a framework that vocational institutions can utilize to modernize their marketing approaches effectively